Metode Penemuan Hukum dalam Sengketa Ekonomi Syari’ah di Pengadilan Agama Purwokerto - Muhammad Fuad Zain (ITB AAS INDONESIA Surakarta, 2021)
Law No. 3 of 2006 has brought major changes to the Religious Courts, where the jurisdiction covers marriage; inheritance; will; grant; waqf; zakat; infaq; sadaqah; and Islamic economics. The research data comes from interviews of judges on decisions regarding Sharia economic disputes. The author finds that in the legal considerations of the judge in case no. 2074/Pdt.G/2017/PA.Pwt raises the theory that the restructuring of the murabahah financing agreement should not or should not be carried out on debtors who are clearly unable to pay installments in accordance with the agreement and auction off collateral goods that are true and not unlawful acts . While case No. 2449/Pdt.G/2018/PA.Pwt in the Musyarakah contract rejects potential loss by referring to DSN Fatwa No. 43/DSN-MUI/VIII/2014 which states that the amount of compensation in a musharaka contract is the value of real losses that must be experienced in the transaction. Discovery of law by using material and formal legal foundations with interpretation methods of legislation and restrictive methods by limiting or narrowing the interpretation of legislation in the context of prudence so as not to make mistakes in giving decisions.